Pathological gambling in adolescence: a narrative review - Lucia Sideli; Daniele La Barbera; Simonetta Montana; Crocetta Rachele Sartorio; Fabio Seminerio; Mariangela Corso; Serena Giunta; Giuseppe Mannino; Caterina La Cascia (Mediterranean Journal of Clinical Psychology, 2018)
Pathological gambling is an emerging and increasing phenomenon in Western counties. This work is aimed at reviewing the existing literature on this topic, paying special attention to its development, course and outcome in adolescence. We will explore epidemiological data, the instruments for the diagnostic and clinical assessment, the course and the outcome of the disorder, the comorbidity with other psychiatric syndromes and disorders. The main risk factors will be described at individual, social and community level. We provide an overview of the available pharmacological and psychological treatments and we report a clinical vignette in order to describe the psychological and psychopathological features of pathological gambling in adolescence.